Testimonial injustice as a way of making up people: an ontological approach - Vilatta, Emilia (2021)
The purpose of this paper is to develop an ontological reading of the ethical and epistemic phenomenon that Miranda Fricker (2017) describes as testimonial injustice. In order to do this, we will resort to the ideas put forward by Ian Hacking (2001, 2002, 2006) concerning the relations between social classifications and social kinds. On the one hand, we will deal with the processes that Hacking terms “making up people”, namely, processes in which the articulation of certain classifications make possible to existence of certain types of people. We will argue that episodes of testimonial injustice, that express the effects of stereotypical classifications, can be construed as part of the social processes of making up people because those episodes contribute to fabricate the epistemic attributes, such as credibility, of certain types or kinds of people. On the other hand, in order to conceptualize the ontological setting under which the phenomenon of testimonial injustice becomes recognizable and reproachable, we will draw on Hacking’s idea of “interactive kinds”. We contend that the concept of “interactive kinds” underlines the fundamentally unstable nature of human kinds and that emphasizing this dynamic aspect can illuminate the social conditions that make testimonial injustice ethically blameworthy. In this sense, we will argue that testimonial injustice can become the object of a normative point of view only insofar as the kinds whose existence is made possible by stereotypical classification are already undergoing a process of change.